Spontaneous alveolo-pleural fistula in a case of COVID-19 pneumonia-challenges and solutions: case report - Singla, Ashita; Gupta, Sanjay; Khan, Washim Firoz (International Surgery Journal, 2021)
COVID-19 pneumonia has demonstrated a wide spectrum of clinical presentations that have yet to be completely uncovered. As this pandemic progresses, uncommon presentations of this disease have come into light. Development of broncho/alveolo-pleural fistula in a patient with COVID-19 pneumonia is a rare phenomenon with only 4 cases reported in literature till date. A 61-year-old gentleman presented to the emergency department with fever, cough, and shortness of breath. His initial chest X-ray was suggestive of a viral pneumonia that was later confirmed to be due to COVID-19. The patient was put on non-invasive ventilator support and treated with empirical antibiotics, glucocorticoids, anti-viral medications and convalescent plasma therapy. Four weeks into the patient’s hospital course, his vital parameters suddenly deteriorated with a subsequent chest X-ray showing a tension pneumothorax, for which a chest tube insertion was done. However, when the air leak did not resolve by the 3rd day, a chest computed tomography (CT) was planned which showed a spontaneous alveolo-pleural fistula (APF). The patient was managed with conservative treatment using negative suction applied to an underwater seal, had his chest tube removed 10 days later and was discharged subsequently. Spontaneous fistulisation between broncho-alveolar tree and pleura can occur rarely in patients with COVID-19 pneumonia and can be managed using underwater seal with negative suction, insertion of endobronchial valves or surgical closure, and needs to be individualised.